A bridge of sustainable urban greening - Huang, Zhao (2007)
Urban growth causes various environmental problems. In order to ameliorate this problem, the idea of the compact city has been introduced nowadays. However, densification can imply a loss of other important urban quality factors, such as green spaces. And high pressures has been input. A disconnection of urban green structure. Parks, green spaces and trees are more than the "lungs of the city" or "pollution scrubbers". They affect our everyday moods, activities and emotional health. They improve our quality of life in ways that are sometimes understood, often underestimated. Whether we are active in urban nature (planting trees, growing gardens) or passively encounter city green (such as a stroll through a park), we experience personal benefits that affect how we feel and function. Proof of psychological and social benefits gives us more reasons to grow more green in cities in a sustainable ecological human way! In this master thesis, main focus is on the roles of green structure in the urban environment with a real case analysis. A theoretical study is carried to review the functions of the green network within cities. In the case of Frederiksberg Park, Copenhagen, Denmark,and Västra Hamnen Bo01, Malmö, Sweden. By several approaches which has been used in the study to discover the underlying problematic and potentials of green structure. The two landscapes with different properties, traditional classical landscape in a historical context (central of city) and contemporary landscape in a brand new context (fringe of city). To analysis these two totally different situations. Furtherly to visualize new developmental plans by combining of both paradigms based old context on sustainable ecological point of view.